Bioelectrochemical system as an innovative technology for treatment of produced water from oil and gas industry: A review. (December 2021) - Cabrera, Jonnathan; Irfan, Muhammad; Dai, Yexin; Zhang, Pingping; Zong, Yanping; Liu, Xianhua
Abstract: Disposal of the high volume of produced water (PW) is a big challenge to the oil and gas industry. High cost of conventional treatment facilities, increasing energy prices and environmental concern had focused governments and the industry itself on more efficient treatment methods. Bioelectrochemical system (BES) has attracted the attention of researchers because it represents a sustainable way to treat wastewater. This is the first review that summarizes the progress done in PW-fed BESs with a critical analysis of the parameters that influence their performances. Inoculum, temperature, hydraulic retention time, external resistance, and the use of real or synthetic produced water were found to be deeply related to the performance of BES. Microbial fuel cells are the most analyzed BES in this field followed by different types of microbial desalination cells. High concentration of sulfates in PW suggests that most of hydrocarbons are removed mainly by using sulfates as terminal electron acceptor (TEA), but other TEAs such as nitrate or metals can also be employed. The use of real PW as feed in experiments is highly recommended because biofilms when using synthetic PW are not the same. This review is believed to be helpful in guiding the research directions on the use of BES for PW treatment, and to speed up the practical application of BES technology in oil and gas industry. Graphical abstract: Image 1 Highlights: Bioelectrochemical systems can treat produced water effectively. The recent progress on BES for produced water treatment was summarized. Various parameters which influence the BES performance were analyzed and discussed. This review will be helpful to guide the research directions on the use of BES.